Online Identity of Public Figure Justinus Laksana: Identitas Online Tokoh Publik Justinus Laksana - Ardiansyah, Mohamad Rangga Rizky; Satria, Dimas Ekha Bagas (Universitas Muhammadiyah Sidoarjo, 2025)
Justinus Laksana has successfully created a strong and credible online persona as a football expert, known for his outspoken, critical, and insightful commentary. By leveraging a bold communication style, football-centric content, and consistent messaging, he has effectively managed the challenges of online reputation and audience engagement. Despite facing potential criticism and polarization, Laksana has used these opportunities to spread knowledge, strengthen his reputation, and advance his career in football. This analysis examines how Laksana has built and maintained his digital identity, navigated interactions with a diverse audience, and addressed privacy and reputation concerns in the digital space. The findings suggest that while Laksana has established a powerful online presence, there are critical areas where further strategic measures are necessary to safeguard his personal information and reputation. Highlights: Bold Communication & Branding – Laksana’s outspoken and critical style has strengthened his credibility as a football expert and engaged a dedicated audience. Audience Engagement & Polarization – While his commentary sparks debate and criticism, he leverages these interactions to enhance his influence and spread football knowledge. Reputation & Privacy Management – Despite his strong online presence, further strategic measures are needed to protect his personal information and digital reputation. Keywords: Justinus Laksana, Football, Social Media